KONSEP DIRI REMAJA DIFABEL DI SEKOLAH INKLUSI PEKANBARU (STUDI KASUS PADA SMPN 31 PEKANBARU) - Nirma Redisa; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In general, diffable students will study at special school, but now there is innovation which called inclusive school. Through inclusive school, teenager student can study at public school and interaction with students that has a normal physical and mental. The condition of difable make acceptance from their friends diverse, some people accept them in a good way and be friends with them, but there are some people bullying their deficiency. Good or bad the communication from their environment, will affect teenagers difable self concept. The main purpose of this research is to determined and understand the perceptual components, the conceptual components, the attitude components and communication experience of diffable teenagers in SMPN 31 Pekanbaru.This research used qualitative research method with phenomenology. Subject in this research were three people. Technique to collect data was through observation, interview, and documentation. This research used data validation technique through the extend of participation and triangulation.The result of this research explained that diffable teenagers in SMPN 31 had diverse self concept. In the perceptual component, the positive side were their physical looks normal, showed neat and beatifull appearance and thinking that they were pretty and had ideal body. While negative side were they felt different from their friends. Then the conceptual components, teenager had positive self concept were confident, independent, be responsible, diligent and polite. The negative side were shy, lazy, unconfident, and spoiled. In the attitude component the positive side were diffable teenager able to socialize, friendly and easy to interact. But the alienated and distinguished feeling were the negative side. And then diffable teenager had a pleasure communication experience was like had happy and proudly feeling, be accepted, given attention and motivation. But also they had a bad communication experience was like insulted, be damned and their friends taken forcibly their money at school.Keywords : self concept, teenager, diffable, inclusive school